Studies on the Pathogenesis of the Generalized Shwartzman Reaction - Rodríguez-Erdmann, F (Thrombosis and Haemostasis, 1964)
The rôle of the clotting system in the pathogenesis of the generalized Shwartzman reaction (gSr) has been stressed in recent years. The clotting system is activated ubiquitously and as a result of it, fibrin is deposited intravascularly and a haemorrhagic diathesis develops. Evidence is presented herein, that endotoxin does not activate purified prothrombin, nor does endotoxin influence the convertion of prothrombin when it is activated in the presence of purified platelet-factor 3 (or caephalin) purified Ac-G (factor V) and Ca-ions.The trigger mechanism of the gSr also seems to be in the so-called prephase of clotting mechanism. Data are presented, which show that endotoxin activates the Hageman factor in vitro. The importance of this clotting factor and of platelet-factor 3 is discussed. Also the rôle played by the RES and cardiodynamic and vascular components are taken in consideration in the discussion.